Determinants Of Climate Change Adaptation Among Male And Female Headed Farm Households In Eastern Uganda - Nabikolo, D.; Bashaasha, B.; Mangheni, M.N.; Majaliwa, J.G.M. (African Crop Science Journal, 2012)
Adaptation is considered an appropriate response to climate change and variability, especially for the smallholder farmers. However, the response decisions and actions of male and female farmers may be influenced by various factor and factor combinations that are not adequately understood. We hypothesized that both male and female farmers are climate change conscious and responsive; and that there is a gender dimension to the choice of a climate change adaptation strategy. We utilised a combination of descriptive statistics and logistic regression analysis to study the factors that influence the choice of a decision to adapt to a climate change scenario. Using cross-sectional data collected from 136 households in eastern Uganda, we undertook the analysis at two levels; pooled sample analysis and a gender disaggregated analysis. Contrary to perceived wisdom and evidence from other empirical studies, the factors that influence the climate change adaptation decision vary considerably between male and female household heads. Climate change adaptation decisions of female heads depended on and were sensitive to more covariates compared to the decisions of male heads of household. Furthermore, climate change adaptation decisions of female heads were influenced by more liquid household assets, while those of male heads were influenced by real estate, especially land. Additionally, beyond gender, other demographic factors appeared to play no significant role in the decision to adapt to climate change.
Keywords: Adaptation decision, gender dimensions, liquid assets